Pengaruh Motivasi, Etos Kerja dan Kompensasi Terhadap Kinerja Karyawan di PT. Nirvana Duta Adijaya (G Trans Logistic) Makassar - Yusman Sutoyo (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
The phenomenon in employee performance issues is an important factor because employee performance will greatly influence the success and progress of a company. The purpose of this study was to determine and analyze the effect of motivation, work ethics, and compensation on employee performance at PT. Nirvana Duta Adijaya (G Trans Logistics) Makassar. The population is 52 people with a sample of 52 employees of PT. Ambassador of Nirwana Adijaya Makassar. Model of data analysis using multiple linear regression analysis, t test, F test and test the coefficient of determination. The results of multiple linear regression testing obtained the formula Y = 7.904 + 0.223 X1 + 0.222 X2 + 1.433 X3. The results of the F test are seen from the significant value of F = 0.000 <0.05 indicating that motivation, work ethic and compensation simultaneously affect employee performance. Based on the results of the T test, motivation has a positive and significant effect on employee performance partially. This is evidenced by the significance level 0.023 <0.05 and the Ha1 hypothesis is accepted. Work ethic has a positive and insignificant effect on employee performance partially. This is evidenced by the level The significance obtained is 0.476 > 0.05 and the hypothesis Ha2 isrejected.Compensation has a positive and significant effect on employee performance partially, this is evidenced by a significance level of 0.000 <0.05 and the hypothesis Ha3 is accepted.